Impact of Celebrity Endorsement on the Purchasing Intentions among Young Adults in Malaysia - Chen, Can (2014)
The ongoing public fascination with celebrities today offers marketers a wide range of creative ideas to attract and charm audience and stimulate their urges to buy (purchasing intentions). Celebrity endorsement has established itself as one of the most popular tools of advertising in recent years. Indeed, it has become something of a fashion, and is often perceived as a winning marketing formula. However, while it is relatively easy to get a celebrity to endorse a product, it is much more difficult to ensure that this will attract consumers and draw their interest in buying that product. This research seeks to evaluate the impact of celebrity endorsement on the purchase intentions of young adults in Malaysia. It examines the relationship between certain key attributes of celebrity endorsers – based on the TEARS model – and consumers’ purchase intentions. These attributes are: trustworthiness, expertise, physical attractiveness, respect and similarity. The study adopts a quantitative approach, with a structured questionnaire as the main tool. SPSS software was used for the descriptive analysis, while One-Way ANOVA, Independent T-test and PLS estimation software were used to test the relationships between the various constructs. The research findings, based on a survey of 318 young adults aged between 18 and 25, show that four of these five TEARS attributes significantly influence consumers’ purchase intentions: but that one, expertise, does not.